Good Governance Dimensions in Teaching Hospitals in Iran: A Thematic Analysis - Javani, Ali; Jamali, Akhtar; Gholi Ghoorchian, Nader (Researcher Bulletin of Medical Sciences, 2025)
Objective: Teaching hospitals have the main role in the health system in developing countries to achieve universal coverage and health equity. This research was aimed to identifying the dimensions of good governance in teaching hospitals in Iran. Materials and Methods: This research was a qualitative study using thematic analysis. The study population were included managers, leaders and policy makers, Service providers and experts and faculty members of teaching hospitals. Sampling was done purposefully and with the convenience method. Data collection was done using a semi-structured interview. The Brown and Clark method was used in data analysis. To ensure and trustworthiness of the qualitative findings, external audit, long-term involvement in the data, peer check, and participant respondent were used. Data analysis was done using Max.qda 22 software. Results: Fifteen main themes, 41 sub-themes and 145 codes were extracted from qualitative data analysis. The main themes identified include transparency, management of conflicts of interest and corruption, social accountability, legal factors, social political participation, determining the role and functional area, how to implement policies, policy evaluation factors, educational challenges of the hospital, fulfilling the goals of stakeholders, ethical factors and values, economic accountability (financial factors), educational indicators, service delivery indicators and the rule of law indicators. Conclusion: Transparency in educational hospitals is the main issue in good governance, so attention should be paid to transparency of costs, transparency of revenues, transparency of payments and even transparency of incentive mechanisms